Revelação e ocultamento: dos estudos sobre violência e violência escolar aos estudos sobre bullying - Castro, Larissa Leão de (2015)
This work, developed in the research line Foundations of Educative Processes, investigated the change from the concept of violence to the trends which prevail in the reconfiguration of its discussion in schools with the term school violence until the development of the term bullying in the scientific production. It aims at understanding what this conceptual change, and particularly, the development of the terminology bullying, reveals and/or hides about violence in schools, by means of the scientific productions in Brazil. Discussing the phenomenon of violence and the way it is treated justifies itself by the importance of reflecting on and overcoming the logico-historical processes which produce, sustain and legitimize violence. The study is based on a structural perspective of discussion of the phenomenon of violence in the broad sense and of school violence in particular, and deals with this phenomenon as a totality, articulating the psychic and social mediations which constitute it. It reads the problem from Freud, Adorno, Horkheimer, Zaluar, Souza, Rodrigues, Zuin, among other authors who work on totality categories and seek the analysis of the main deciding and constituent mediations of the analyzed question, either by means of the analysis of culture, of the constitution of the subject, of history, work, economic organization, or school. A bibliographical research produces the status quaestionis of the production of theses and dissertations on school violence and bullying in Brazil between 2005 and 2012, by understanding the reconfiguration of the discussion of violence in schools until the development of the term bullying and expounds a comparative analysis both of the trends of the scientific production of theses and dissertations on school violence and of the trends of the scientific production on bullying in Brazil. Finally, it analyzes, internally and comparatively, these prevailing trends with the perspective of discussing violence in the broad sense and its relation with school. Moreover, it analyzes the trends of previous knowledge developing in history, aiming at understanding the implications of this change. The research postulates that there is a dimension of rupture between the prevailing trends in the studies on school violence and bullying with the studies on violence in the broad sense, which are based on theories of totality in the analyses and its relation with school education. This change implies a rupture of conceptions and epistemological interests, presuppositions, currents of thought, explicit or implicit political commitments and interventions against the problem, which not only tends to hide what it generates, and to sustain violence in the society, but also tends to legitimize it by means of such hiding.